Psychoeducation for depression, anxiety and psychological distress: a meta-analysis - Donker, Tara (BioMed Central, 2009)
BACKGROUND: Given the high prevalence and burden associated with depression and anxiety disorders and the existence of treatment barriers, there is a clear need for brief, inexpensive and effective interventions such as passive psychoeducational interventions. There are no published meta-analyses of the effectiveness of passive psychoeducation in reducing symptoms of depression, anxiety or psychological distress. METHODS: Cochrane, PsycInfo and PubMed databases were searched in September 2008. Additional materials were obtained from reference lists. Papers describing passive psychoeducational interventions for depression, anxiety and psychological distress were included if the research design was a randomized controlled trial and incorporated an attention placebo, no intervention or waitlist comparison group. RESULTS: In total, 9010 abstracts were identified. Of these, five papers which described four research studies targeting passive psychoeducation for depression and psychological distress met the inclusion criteria. The pooled standardized-effect size (four studies, four comparisons) for reduced symptoms of depression and psychological distress at post-intervention was d = 0.20 (95% confidence interval: 0.01-0.40; Z = 2.04; P = 0.04; the number needed to treat: 9). Heterogeneity was not significant among the studies (I(2 )= 32.77, Q:4.46; P = 0.22). CONCLUSIONS: Although it is commonly believed that psychoeducation interventions are ineffective, this meta-analysis revealed that brief passive psychoeducational interventions for depression and psychological distress can reduce symptoms. Brief passive psychoeducation interventions are easy to implement, can be applied immediately and are not expensive. They may offer a first-step intervention for those experiencing psychological distress or depression and might serve as an initial intervention in primary care or community models. The findings suggest that the quality of psychoeducation may be important.